Micro-political aspects of mandate development and learning in local subsidiaries of multinational corporations - Christoph Dörrenbächer; Mike Geppert (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2005)
Beyond functional-structuralist approaches this paper sheds some light on micro political aspects of mandate development and learning processes in multinational corporations (MNC). As classical micro-political studies have shown, management behaviour and learning are not only constrained or enabled by certain structural and (national) cultural patterns, but have its own political agendas and are shaped by individual interests which leads to game playing, active or passive resistance and (re)negotiation of the 'rules of the game'. Based on the assumption that actors are neither the organs of given structures nor acting fully autonomous, the paper focuses on how subsidiary managers interpret and integrate individual, organisational as well as home and host country institutional factors into certain strategies of action. By discussing critical events in mini case studies on mandate development and learning in German subsidiaries in France we will highlight the interactive dynamics between key-actors micro-political strategies and particular institutional settings. Here we, firstly, discuss institutionalist approaches and investigate how different forms of home and host country embeddedness do influence the development of distinct managerial competences and decision making strategies at the subsidiary level. The paper refers then to the question how the overall strategy and multinational organisational design and policies relate to individual interests of key subsidiary actors. These can to higher or lower degrees be influenced by e.g. differences in nationalities, professional backgrounds as well as career stages, orientations and aspirations. By integrating these diverse relational layers, the paper will provide a more dynamic actor centred approach stressing both, the micro-political aspects and interactive construction of intra and intersubsidiary power relations, a key variable to explain mandate development and learning processes in MNCs. – – Über funktional-strukturalistische Ansätze hinausgehend, beschäftigt sich dieser Beitrag mit den mikropolitischen Aspekten von Mandatsentwicklungsprozessen in multinationalen Unternehmen. Im Zentrum der Betrachtung stehen die Strategien und Handlungsrationalitäten von Tochtergesellschaftsmanagern im Ausland. Anhand von drei Fallbeispielen zeigt der Beitrag wie Manager deutscher Auslandsgesellschaften in Frankreich individuelle, organisationale und institutionelle Faktoren (Heimat- und Gastlandeffekte) interpretieren und zu einer Handlungsstrategie verbinden. Ausgangspunkt ist dabei zunächst eine Diskussion relevanter Ansätze des Internationalen Managements und der international vergleichenden Organisationsforschung. Diese Ansätze werden um einen mikropolitischen Ansatz erweitert, der auf die spezifische Bedeutung von Nationalzugehörigkeit, professionellem Background und individueller Karriereorientierung bei Tochtergesellschaftsmanagern im Ausland abstellt.
Keywords: 650; Auslandsniederlassung; Deutsch; Führungskräfte; Lernprozess; Mikropolitik; Theorie; Frankreich